From the Public Space to the Prison Space: Regulation Polemic and the Implementation of Caning Law in Aceh - Mizaj Iskandar; Azhari Yahya; Abdul Jalil Salam; Junaidi (Faculty of Sharia IAIN Madura collaboration with The Islamic Law Researcher Association (APHI), 2022)
The implementation of caning law in Aceh Province is still sporadic due to a lack of coordination among the government institutions involved in caning law. Then, the prison infrastructure to impose the canning law is also not ade-quate, and socialization has also not been fully carried out. Besides, in deter-mining the location of the caning, Islamic law requires the fulfillment of two principles namely “open space” and “visible” to the public. Furthermore, the law that guides the implementation of sharia in Aceh does not regulate detail of where the caning can be executed. Hence, the issues that need to be scruti-nized in this study are about shifting the norm from “open space